Peningkatan Kualitas Pencatatan dan Pelaporan Data Pelayanan Posyandu Balita Sari Kencana 1 dan 2 di Desa Pentur Simo Boyolali - Yeni Tri Utami; Siti Farida (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Posyandu is a forum between professional services from health workers and community participation in overcoming public health problems, especially in efforts to reduce infant mortality. According to the 2022 Central Statistics Agency (BPS) report, Indonesia has an infant mortality rate of 16.9 per 1,000 live births. Posyandu Sari Kencana 1 dan 2 and 2, Pentur Village, Simo, and Boyolali shelter 2 RWs consisting of 5 RTs, namely RT 001–RT 005, with a total of 60–80 toddlers. This Posyandu has 10 cadres who assist in the process of implementing activities. In implementation, problems were found regarding a lack of service quality, especially data recording, which was still manual and unsystematic. In this service activity, service records are implemented into the posyandu register book (printed) and Ms. Exel and toddler posyandu cards for recording and reporting, which can be used to help posyandu performance in data and information management so that it can be carried out clearly, regularly, and quickly, which can later support smooth operations and policy making.